Variability in cTBS Aftereffects Attributed to the Interaction of Stimulus Intensity With BDNF Val66Met Polymorphism - Harvey, Denise Y.; DeLoretta, Laura; Shah-Basak, Priyanka P.; Wurzman, Rachel; Sacchetti, Daniela; Ahmed, Ahmed; Thiam, Abdou; Lohoff, Falk W.; Faseyitan, Olufunsho; Hamilton, Roy H. (Frontiers in Human Neuroscience, 2021)
Objective: To evaluate whether a common polymorphism (Val66Met) in the gene for brain-derived neurotropic factor (BDNF)—a gene thought to influence plasticity—contributes to inter-individual variability in responses to continuous theta burst stimulation (cTBS), and explore whether variability in stimulation-induced plasticity among Val66Met carriers relates to differences in stimulation intensity (SI) used to probe plasticity. Methods: Motor evoked potentials (MEPs) were collected from 33 healthy individuals (11 Val66Met) prior to cTBS (baseline) and in 10 minute intervals immediately following cTBS for a total of 30 min post-cTBS (0 min post-cTBS, 10 min post-cTBS, 20 min post cTBS, and 30 min post-cTBS) of the left primary motor cortex. Analyses assessed changes in cortical excitability as a function of BDNF (Val66Val vs. Val66Met) and SI. Results: For both BDNF groups, MEP-suppression from baseline to post-cTBS time points decreased as a function of increasing SI. However, the effect of SI on MEPs was more pronounced for Val66Met vs. Val66Val carriers, whereby individuals probed with higher vs. lower SIs resulted in paradoxical cTBS aftereffects (MEP-facilitation), which persisted at least 30 min post-cTBS administration. Conclusions: CTBS aftereffects among BDNF Met allele carriers are more variable depending on the SI used to probe cortical excitability when compared to homozygous Val allele carriers, which could, to some extent, account for the inconsistency of previously reported cTBS effects. Significance: These data provide insight into the sources of cTBS response variability, which can inform how best to stratify and optimize its use in investigational and clinical contexts.